PENGARUH MEDIA FLASHCARD DALAM MENINGKATKAN MUFRODAT SISWA KELAS X MAN 2 BANDAR LAMPUNG - Hanifah, Suvi; Fauziah, Asti; Kesuma, Guntur; Malik, Adam (Penerbit Lafadz Jaya, 2026)
This study examines the effect of flashcard media on improving students’ Arabic vocabulary (mufrodat) mastery at grade X of MAN 2 Bandar Lampung. The research employed a quantitative approach using a one-group pretest–posttest design. The sample consisted of 30 students from class X A selected through cluster sampling. The research instrument was a 40-item vocabulary test validated through expert judgment. Data were analyzed using descriptive statistics and a paired samples t-test. The results showed that the mean pretest score of 68.8 increased to 87.7 in the posttest. The paired samples t-test results indicated a significance value of 0.000 < 0.05, demonstrating a statistically significant difference between pretest and posttest scores. Therefore, it can be concluded that flashcard media has a significant effect on improving students’ Arabic vocabulary mastery.